Increasing Knowledge About History of Hindu Empire in Indonesia with Game “Indo Trivia” - Pieter Theodorus Handoko; Erdhi Widyarto Nugroho; Bernadinus Harnadi (Soegijapranata Catholic University, 2022)
Most young people think that History is not important enough to learn and they are more likely to choose to play games. This study aims to develop the game